Virtual atmosphere: the effect of pleasure, arousal and delight on word-of-mouth - Loureiro, S. M. C.; Ribeiro, L. (Journal of Promotion Management, 2014)
This study investigates the effect of virtual atmospheric cues on emotions and word-of-mouth and also analyzes the differences between the perceptions of male and female participants relative to the online environment. Questionnaires were given to students in higher education and senior university students. The main findings suggest that pleasure is the most effective emotion to lead to a positive word-of-mouth for both genders. Women are more willing to say positive words to others than men. Women are also more influenced by the delight and pleasure, whereas men are influenced only by pleasure